Functional Oligosaccharides: Research Progress in Preparation, Function, and Application - Benedek, Tiamor; Ruiz, Irma; Iranzo , Salvada (Journal of Green Energy and Environmental Engineering, 2025)
Functional oligosaccharides are increasingly gaining public attention due to their various significant health benefits and have found numerous applications in areas such as health foods. However, the quantitative use and safety analysis of functional oligosaccharides still lack effective and extensive data support. The author, through methods including literature review, industry research, comparison of domestic and international regulations, and integration of health evidence with experimental results, summarizes the research progress of three common functional oligosaccharides regarding their sources, production processes, safety, dosage, and their application in health foods. The existing issues within the functional oligosaccharide industry are also discussed.